Generalized Differential Quadrature Finite Element Method for vibration analysis of arbitrarily shaped membranes - Fantuzzi, Nicholas; Tornabene, Francesco; Viola, Erasmo (International journal of mechanical sciences, 2014)
This paper provides a new technique for solving free vibration problems of composite arbitrarily shaped membranes by using Generalized Differential Quadrature Finite Element Method (GDQFEM). The proposed technique, also known as Multi-Domain Differential Quadrature (MDQ), is an extension of the classic Generalized Differential Quadrature (GDQ) procedure. The multi-domain method can be directly applied to regular sub-domains of rectangular shape, as well as to elements of general shape when a coordinate transformation is considered. The mapping technique is used to transform both the governing differential equations and the compatibility conditions between two adjacent sub-domains into the regular master element in the parent space, called computational space. The numerical implementation of the global algebraic system obtained by the technique at issue is simple and straightforward. Computer investigations concerning a large number of membrane geometries have been carried out. GDQFEM results are compared with those presented in the literature and a perfect agreement is observed. Membranes of complex geometry with a material inhomogeneity are also carefully examined. Numerical results referring to some new unpublished geometric shapes are reported to let comparisons with further research on this subject. •Free vibrations of arbitrarily shaped composite membranes with complex geometries.•Generalized Differential Quadrature applied within coordinate transformation.•Stability, convergence and accuracy study performed for the GDQFEM.•New complex geometries of composite membranes proposed for further developments.